PENGARUH OPINI AUDIT TAHUN SEBELUMNYA, OPINION SHOPING, KESULITAN KEUANGAN, AUDITOR CLIENT TENURE, KUALITAS AUDIT TERHADAP OPINI AUDIT WAJAR TANPA PENGECUALIAN DENGAN PARAGRAF PENJELAS (GOING CONCERN) - Rivelino, Dhani Yudhi; Sari, Ria Nelly; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Indonesia's economic problems a few years led many companies to Property & Real Esatate experienced instability due to the influence of the global financial crisis, causing substantial doubt on the ability of companies (Unqualified opinion report with explanatory paragraph/Going Concern). Substantial doubt consists of two problems, namely financial issues and problems in the operation of the company. So the purpose of this study was to determine the effect of opinion audit last year, shoping opinion, financial distress, the client auditor tenure, audit quality on wtp audit opinion with an explanatory paragraph on company property and real estate in Indonesian stock exchange. The population of this research is company property and real estate in Indonesian stock exchange. Sampling by purposive sampling, and obtained 22 corporate data into a sample for the study year 2010-2011. The method used is descriptive analysis and logistic regression analysis using SPSS (Statistical Package for Social Science) 20. From the analysis show that opinion audit last year significantly affect on Unqualified opinion report with explanatory paragraph/Going Concern). While the quality of the audit, opinion shopping, financial distress, the client auditor tenure no significant effect on (Unqualified opinion report with explanatory paragraph/Going Concern). Keywords: Opinion Audit Last Year, Opinion Shopping, Financial Distress, Auditor Client Tenure, Audit Quality.